Analysis of Characteristics and Feasibility Test of “Swara Kretek” Costumes: Manifestation and Aesthetics of Kudus Kretek Dance - Putri, Puja Rahmatika Lingga; Kusumastuti, Adhi (Journal of Creativity Student, 2026)
The rapid pace of modernization poses a challenge to local cultural identity, particularly the heritage of Kretek dance in Kudus. This study aims to analyze the design characteristics, reveal its symbolic meaning, and evaluate the feasibility of the “Swara Kretek” costume, an innovative transformation of dance aesthetics into premium clothing. This study uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection was conducted through a literature study, while feasibility testing used a Guttman-scale instrument validated by three fashion design expert validators. The results show that “Swara Kretek” successfully embodies the Exotic Dramatic style with an H silhouette, integrating manual weaving and the Tohwatu Shawl through a 3D hanging overlay technique to represent the mbathil and ngiteri movements. The feasibility test yielded an average score of 95.19%, placing the product in the “Highly Feasible” category. This proves that “Swara Kretek” successfully synergizes traditional philosophy with modern industry standards, making it ready for professional exhibition and production in the premium ethnic fashion market.